2022
DOI: 10.3390/biomedicines10092118
|View full text |Cite
|
Sign up to set email alerts
|

Revertant Mosaicism in Genodermatoses: Natural Gene Therapy Right before Your Eyes

Abstract: Revertant mosaicism (RM) is the intriguing phenomenon in which nature itself has successfully done what medical science is so eagerly trying to achieve: correcting the effect of disease-causing germline variants and thereby reversing the disease phenotype back to normal. RM was molecularly confirmed for the first time in a genodermatosis in 1997, the genetic skin condition junctional epidermolysis bullosa (EB). At that time, RM was considered an extraordinary phenomenon. However, several important discoveries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…Finally, the focal nature of adhesion protein downregulation in AEC patient skin suggests the existence of mechanisms that restore or maintain hemidesmosomal and focal adhesion proteins in the presence of TP63 mutations. There is currently no evidence for the existence of a genetic mechanism, such as revertant mosaicism, 37 to explain this phenomenon. Regardless of the genetic or epigenetic mechanism, the ability to restore adhesion is consistent with the observation that AEC skin erosions heal over time and are generally small or absent in adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the focal nature of adhesion protein downregulation in AEC patient skin suggests the existence of mechanisms that restore or maintain hemidesmosomal and focal adhesion proteins in the presence of TP63 mutations. There is currently no evidence for the existence of a genetic mechanism, such as revertant mosaicism, 37 to explain this phenomenon. Regardless of the genetic or epigenetic mechanism, the ability to restore adhesion is consistent with the observation that AEC skin erosions heal over time and are generally small or absent in adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…At first considered a rare phenomenon, revertant mosaicism was, in a later study, shown to be present in the majority of patients with COL17A1-associated JEB; it has subsequently been detected in all major EB subtypes [14,15]. Although a proof of principle transplantation of autologous revertant keratinocytes was successfully performed on a laminin-deficient patient, several obstacles, including the isolation of revertant stem cells, need to be addressed before it can provide a safe and efficient therapeutic treatment option [15,16].…”
Section: Eb Therapeutics Under Development 21 Autologous and Allogeni...mentioning
confidence: 97%
“…Specifically, revertant mosaicism has been reported in epidermolysis bullosa simplex due to KRT14 mutations [ 91 , 92 , 93 ]. It might be hypothesized that revertant mosaicism exists among clinical manifestations of the NFJS [ 94 ].…”
Section: Dermatopathia Pigmentosa Reticularismentioning
confidence: 99%